Development of mesoporous silica-based nanoparticles with controlled release capability for cancer therapy() - Mekaru, Harutaka (Adv Drug Deliv Rev, 2015)
Nanoparticles that respond to internal and external stimuli to carry out controlled release of anticancer drugs have been developed. In this review, we focus on the development of mesoporous silica based nanoparticles, as this type of materials provides a relatively stable material that is amenable to various chemical modifications. We first provide an overview of various designs employed to construct MSN-based controlled release systems. These systems respond to internal stimuli such as pH, redox state and the presence of biomolecules as well as to external stimuli such as light and magnetic field. They are at a different stage of development; depending on the system, their operation has been demonstrated in aqueous solution, in cancer cells or in animal models. Efforts to develop MSNs with multi-functionality will be discussed. Safety and biodegradation of MSNs, issues that need to be overcome for clinical development of MSNs, will be discussed. Advances in the synthesis of mechanized theranostic nanoparticles open up the possibility to start envisioning future needs for medical equipment.